2022
DOI: 10.3389/fmed.2022.856260
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cardiovascular Risk Burden on Motor Function Among Older Adults: Mediating Role of Cardiovascular Diseases Accumulation and Cognitive Decline

Abstract: PurposeThis study aimed to investigate the association of the cardiovascular risk burden assessed by the Framingham General Cardiovascular Risk Score (FGCRS) with the trajectories of motor function over time and to assess the mediating effects of cardiovascular diseases (CVDs) accumulation and cognitive decline in such association.MethodsIn Rush Memory and Aging Project, a total of 1,378 physical health participants (mean age: 79.3 ± 7.3 years) were followed up for up to 22 years. FGCRS at baseline was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…This exposure enables the active ingredients present in Angelica keiskei to exert more potent antioxidant effects on these cells. Furthermore, previous research conducted a 22-year follow-up analysis on 1378 physically healthy participants, with a mean age of 79.3 ± 7.3 years, and found a correlation between higher cardiovascular risk burden in older adults and a faster decline in physical functions, including agility, gait, and hand strength [ 51 ]. It is possible that the enhancement of the musculoskeletal system by Angelica keiskei may be partially attributed to improved cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…This exposure enables the active ingredients present in Angelica keiskei to exert more potent antioxidant effects on these cells. Furthermore, previous research conducted a 22-year follow-up analysis on 1378 physically healthy participants, with a mean age of 79.3 ± 7.3 years, and found a correlation between higher cardiovascular risk burden in older adults and a faster decline in physical functions, including agility, gait, and hand strength [ 51 ]. It is possible that the enhancement of the musculoskeletal system by Angelica keiskei may be partially attributed to improved cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cardiovascular disease may increase the risk of both hearing loss 33 and impaired mobility. 34 While we have attempted to mitigate confounding by controlling for several comorbidities, it is essential to acknowledge that there may be unaccounted-for confounders beyond the scope of the NHIS dataset. 7 Regardless of the underlying mechanism, however, mobility challenges in individuals with hearing loss may exacerbate their overall morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…One must also consider potential confounding factors. For instance, cardiovascular disease may increase the risk of both hearing loss 33 and impaired mobility 34 . While we have attempted to mitigate confounding by controlling for several comorbidities, it is essential to acknowledge that there may be unaccounted‐for confounders beyond the scope of the NHIS dataset 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Gait disturbance is a prevalent chronic disorder among community-dwelling older adults, leading to an increased risk of falls, morbidity, and mortality [ 1 3 ]. Previous studies have shown that an increased cardiovascular risk is associated with impaired gait function, specifically decreased gait speed [ 4 , 5 ]. Carotid atherosclerosis, primarily measured by carotid intima-media thickness (IMT), is associated with a higher risk of gait disorders, such as decreased walking speed and impaired balance ability [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%